EKSISTENSI TRADISI DO’A PADANG DI BANJAR NAN TIGO DESA NAN OMPEK KECAMATAN KUANTAN HILIR KABUPATEN KUANTAN SINGINGI - Warianti, Nurmis; Tantoro, Swis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted in Banjar Nan Tigo Nan Ompek Village, Kuantan Hilir Sub-District, Kuantan Singingi District. This research was conducted to obtain information about the existence of the Padang Prayer tradition in banjar nan tigo nan ompek village with the aim was to find out the process of implementing the Padang Prayer tradition, how to maintain the tradition of Padang Prayer and the meaning of the Padang Prayer tradition in banjar nan tigo nan ompek village. The theory used is George Herbert Mead theory, namely the theory of simbolic interactionism. This research is a survey reasearch using descriptive qualitative methods, data collection by observation and in-depth interviews. The number of informants in this study was 8 people consisting of 1 ninik mamak, 1 alim ulama, 1 village head, 1 village secretary, 1 chief executive, and 3 community members. The results of the study showed that the process of implementing the Padang Prayer tradition was (1) conducting deliberation before the implementation of the Padang Prayer Tradition, (2) do mutual cooperation, and (3) Padang Prayer event on Thursday. Maintaining the tradition of Padang Prayer needs to be done by growing enthusiasm of community participant and the role/cooperation of the government. The meaning of Padang Prayer tradition which is the belief of the banjar nan tigo nan ompek village is as a safety of the community’s agriculture and as a form of togetherness and cohesiveness of the community. Keywords: Existence, Tradition, Padang Prayer